APPLICATION OF PIAGET'S THEORY IN EARLY CHILDHOOD EDUCATION CURRICULUM DEVELOPMENT - Aslan Aslan; Hudson Sidabutar (Adisam Publisher, 2026)
The application of Jean Piaget's cognitive development theory in early childhood education curriculum development plays an important role in creating learning programmes that are appropriate to children's developmental stages. Piaget's theory, which identifies sensorimotor, preoperational, concrete operational and formal operational stages, offers guidance for educators to design appropriate educational activities that support children in each stage of development. Learning through direct experience and play activities, in accordance with Piaget's principles, allows children to learn through interaction with their environment, reinforcing understanding and skills naturally. This approach not only makes the learning process more interesting and relevant for children, but also ensures that the concepts taught are appropriate for their cognitive abilities. The implementation of Piaget's theory in the curriculum also emphasises the early development of critical thinking and problem-solving skills, which are important for intellectual development and readiness to face future challenges. Thus, Piaget's theory contributes significantly to shaping a curriculum that is adaptive, child-centred and effective in supporting children's holistic development early in their educational journey.